2014
DOI: 10.1530/erc-13-0436
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic profiling in thyroid cancer provides clues for failure of tumor immunity

Abstract: Thyroid cancer is usually surrounded by a significant number of immune reactive cells. Tumor associated lymphocytes as well as background lymphocytic thyroiditis is frequently mentioned in pathology reports of patients operated for thyroid cancer. The nature of this lymphocytic reaction in not well understood. Evidently, the fact that cancer can survive in this adverse microenvironment speaks for immune regulation. We characterized the lymphocytic infiltration that accompanies thyroid cancer and compared it to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 35 publications
3
49
0
1
Order By: Relevance
“…Cancer immunoediting has been reported for other human cancers already (26). Further studies are needed to assess the types of immunity involved in the different forms of HT, and their effect on thyroid cancer development or vice versa (27).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer immunoediting has been reported for other human cancers already (26). Further studies are needed to assess the types of immunity involved in the different forms of HT, and their effect on thyroid cancer development or vice versa (27).…”
Section: Discussionmentioning
confidence: 99%
“…This double negative lymphocyte population was identified as the dominant cell type in PTC and was more abundant in PTC than in thyroid autoimmunity. 106 These cells ex vivo released IFNg and IL-17, thus resembling effector cells.…”
Section: Natural Killer T Cells (Nkt) Gd T Cells and Innate Lymphoidmentioning
confidence: 98%
“…Based on investigation of frozen tissue sections and flow cytometry (Imam et al 2014), they showed that CD3+, CD4− and CD8− lymphocytes were significantly more abundant in PTC (>20%) compared with autoimmune thyroiditis (<5%). Moreover, after PMA/Ionomycin stimulation, the population of CD3+, CD4− and CD8− lymphocytes derived from PTC patients remained unchanged, but increased in samples derived from thyroid autoimmunity patients.…”
Section: :10mentioning
confidence: 99%